Fundamental trading strategies in frontier markets - Jantunen, Anton (My University, 2014)
This thesis aims to be the first paper to study non normalized and industry normalized fundamental trading strategies in the frontier markets. Specifically, I test whether book-to-market (B/M), earnings-to-price (E/P), dividend-to-price (D/P), and EBITDA-to-enterprise value (E/E) strategies can create constant abnormal returns in the frontier markets.
Keywords: Frontier; markets; portfolio; strategy; industry; normalization; fundamental; valuation; alpha; value; rahoitus; financing; sijoitukset; investments; strategia; strategy; portfolio; portfolio; tuotto; rate of return